The Millennial generation and national defense attitudes of future military and civilian leaders - Ender, Morten G.; Rohall, David E.; Matthews, Michael D. (Palgrave pivot, 2014)
Captures the views, values, and attitudes of today's youth -- the Millennial generation -- towards the military, war, national defense and foreign policy matters.